Analisis Usability pada Situs Perpustakaan UC dengan Menggunakan System Usability Scale - Maryati, Indra; Nugroho, Elisabeth Inez; Indrasanti, Zefanya Oktaviana (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2022)
During the Covid-19 pandemic, libraries have been severely impacted by a decline in visitors. Universitas Ciputra’s Library (UC Library) has its own website outside the main university website, but the initial page does not reflect much on the main function of the library which provides collections that are available and accessible to users. To revive the function of the UC Library site to be useful and empowered for the UC academic community, it is necessary to revitalize it. The level of usability is very influential for the sustainability of a system, and in this study it can certainly be useful for initial data on the revitalization process. One method to measure usability that is often used is the System Usability Scale (SUS). SUS was developed by John Brooke since 1986. SUS is a usability scale that is reliable, popular, effective, and inexpensive. Users of the UC Library site were given 10 questions and answered them using a Likert scale. The results of the calculation of 46 respondents obtained the SUS score obtained is 57.12. This value falls into category F, and this results in a low usability level of the UC Library site and it is very necessary to revitalize it.